CONTEXTUAL TEACHING AND LEARNING BERBANTUAN CD PEMBELAJARAN PADA MATERI BAGIAN-BAGIAN TUMBUHAN DAN FUNGSINYA DI SD - Bahmid Bakar; Moh. Farid Nurul Anwar; Heri Setiawan; Siti Fatimah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
The learning problems that are often encountered are the teacher's lack of mastery of the learning model and the teacher's lack of understanding of the proper use of media, causing students to not understand the subject matter. The use of learning models with the right media can increase student learning activities and outcomes. The learning model used in this lesson is Contextual Teaching and Learning (CTL) assisted by Learning CD media on plant parts and their functions in elementary schools. The learning process takes place referring to the seven components of CTL.